HIGH RISK OF OBSTRUCTIVE SLEEP APNEA, OBESITY, MELATONIN LEVELS, AND C-REACTIVE PROTEIN IN INDIVIDUALS WITH AND WITHOUT DIABETES MELLITUS: A COMPARATIVE STUDY - Indrasari Utami, Desak Ketut; Saraswati, Made Ratna; Ariyanti Putri, Putu Dian; Yustiantara, Putu Sanna; Pikatan, Orlando (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Sleep is a fundamental pillar for maintaining metabolic, endocrine, and cardiovascular stability. However, individuals diagnosed with Type 2 Diabetes Mellitus (T2DM) are disproportionately susceptible to sleep-related disorders, particularly Obstructive Sleep Apnea (OSA). This relationship is often bidirectional, where sleep disturbances can exacerbate insulin resistance and negatively impact the overall prognosis of the disease. Objective: The primary goal of this study was to conduct a comparative analysis between diabetic and non-diabetic individuals regarding sleep quality, OSA risk, and obesity prevalence. Additionally, the research aimed to investigate whether these clinical factors correlated with differences in specific biomarkers, specifically melatonin and C-reactive protein (CRP) levels. Methods: A cross-sectional study was conducted at Ngoerah General Hospital involving 52 participants that fulfilled the eligibility criteria (26 with T2DM and 26 without). Sleep assessment was using the PSQI, Epworth Sleepiness Scale, and STOP-BANG questionnaire. Anthropometric measurements were taken, and blood samples were analysed for melatonin and CRP levels using ELISA. Results: In a cohort of 52 participants (divided evenly into 26 with T2DM and 26 without), significant clinical disparities were observed. The diabetic group demonstrated a much higher prevalence of poor sleep quality (61.5%) compared to the non-diabetic group (26.9%, p=0.012). Similarly, the risk of high-grade OSA was substantially more common among diabetic patients (42.3%) than in the control group (7.7%, p=0.004), with obesity present exclusively in the diabetic cohort (19.2%). Despite these findings, there were no statistically significant differences between the two groups regarding daytime sleepiness, CRP levels (p=0.634), or melatonin concentrations (p=0.194). Conclusion: Patients with T2DM exhibit a significantly higher burden of sleep dysfunction, obesity, and OSA risk compared to individuals without diabetes. However, these physical manifestations did not translate into distinct variations in CRP or melatonin levels in this study. These results highlight the necessity for a holistic approach to diabetes management that actively integrates sleep and circadian health, while suggesting that further longitudinal research is needed to clarify the behavior of these biomarkers over time.